Il reato di bigamia nella Repubblica di Venezia da un processo del 1630 - Andreato, Claudia (Acta Histriae, 2007)
In 17th century Venice bigamy represented a crime of exogamy and mobility with a subversive power against the constituted social order. The offence often involved male and female figures (in trial documents found in the roles of both victims or defendants) that could hardly be included in one of the most common social schemes: the victims were frequently implicitly aware of the risk of getting married to a person with an unknown past; the defendants would deny their identities in order to construct others; and finally, the witnesses seemed to cover with a veil of silence the "individual" choices that concealed behaviour often regarded as deviant. Hence, the rhetoric that animated the trial narrative reflected the multifaceted characteristics attributed to the offence and its protagonists on one hand, and on the other the attempt of the secular and ecclesiastical authorities to preserve the set of moral and religious values in the society of that time
Keywords: 1630; Beneška republika; bigamija; kazniva dejanja; kulturna zgodovina; Republic of Venice